Memahami Desentralisasi Fungsional (Perbandingan Praktek di Belanda, Jepang, USA, dan Jerman) - Maksum, Irfan (UI Scholars Hub, 2021)
Functional decentralisation practices in developing countries are mixed with the so-called privatisation which is a part of economic desentalisation and/or delegatuon of administrative decentralisation. This concept research is important in order to understand the concet of decentralisation as a whole. This article tries to make comparison of functional decentralisation practices in four countries: the Netherlands, Japan, the United States, ang Germany.